Synthesis and Characterization of Poly(Hydroxamic Acid) and Poly(Amidoxime) Chelating Resins from Polymer Grafted Sago Starch - Rahman, Md. Lutfor (1999)
The graft copolymerization of methyl acrylate (MA) onto sago starch was performed by free radical initiating process in which ceric ammonium nitrate (CAN) was used as an initiator. It was found that the optimum yield of grafting, grafting efficiency and rate of graft polymerization were all dependent upon the concentration of CAN, MA, sago starch (AGU) and mineral acid (H2S04) as well as reaction temperature and period. A new equation rate of polymerization was derived from the proposed reaction mechanism. A new kinetic model for graft fraction was proposed and the validity of the model was tested by the plot of l/(l-GF)ll2 as a function of sago starch concentration and reciprocal monomer (MA) concentration. The required straight line and ordinate intercept unity was obtained and the predicted kinetic model was satisfactory supported by the experimental results until a certain limit of monomer (MA) concentration. A chelating polymeric resin containing hydroxamic acid was synthesized from poly(methyl acrylate) (PMA) grafted sago starch. The binding capacity of the poly(hydroxamic acid) resin with copper is high and other metal ions also show significant binding capacity. This chelating resin has the advantage of faster rate of equilibrium and negligible affinity for alkali metal ions. The sorption capacities of metal ions were pH dependent and its selectivity towards these metal ions is in the following order: Cu2+ > Fe3+ > Cr3+ > Ni2+ > Co2+ > Zn2+ > Cd2+ > As3+> Pb2+. These paration of Cu2+ from Co2+ and Cd2+, and Fe3+ from Co2+ and Cd2+ were carried out by column technique.